Another Way to Listen: Reflections on Listening in a Narrative Inquiry - Corinne Rogers; Vera Caine (International Journal of Qualitative Methods)
I encountered significant challenges in hearing Phoenix, a participant in a narrative inquiry into the health and well-being of women previously trafficked. My struggles to hear Phoenix lead me to constantly interrupt her. These interruptions were palpable and violent in their silencing. Yet, Phoenix continued to invite me to listen to her, calling me to better understand who I was and who I was becoming alongside her. In this paper, I reflect on ways to listen and the art of listening in narrative inquiry. I illustrate how maintaining a connection is vital for developing different ways of listening, a form of listening that is guided by ethical considerations and responsiveness. I show how listening serves as both a state of being and a mode of thinking within narrative inquiry.